ISSUE PAPER SMOKING IN THE WORKPLACE (Tufts Archival Research Center, 2007)
Tobacco Institute issue paper on smoking in the workplace. Concerns itself with three dimensions of the issue: legislative, judicial and voluntary. Deals with voluntary action taken by employers with economic, sociological, and health arguments. Argues that smokers are not more costly than non smokers, that smoking restrictions are a form of social discrimination, and that research showing a link between secondhand smoke and cancer is not reliable.